IMPLEMENTATION OF DISCIPLINE AND RESPONSIBILITY CHARACTER EDUCATION THROUGH DAILY MUROJAAH CULTURE AT DARUL ISTIQOMAH MAESAN BONDOWOSO ELEMENTARY SCHOOL FOR THE 2024-2025 ACADEMIC YEAR - Shodiq, Fajar; Muhith, Abd.; Matkur, Matkur; Rahman, Yudi Ardian (FORUM PAEDAGOGIK, 2024)
This research examines the implementation of discipline and responsibility character education through the daily murojaah culture at Darul Istiqomah Elementary School, Maesan, Bondowoso, during the 2024–2025 academic year. The murojaah practice, involving daily Quranic recitation and review, is used as a strategy to instill discipline and responsibility in students. Using a qualitative descriptive approach, data were collected through observations, interviews with educators, and document analysis. The findings reveal that the murojaah culture is systematically organized, emphasizing consistency, teacher-student collaboration, and parental involvement, which significantly enhance students' punctuality, focus, and accountability.The study concludes that the daily murojaah culture effectively nurtures discipline and responsibility among students, creating a positive and supportive learning environment. Challenges such as varying levels of student readiness are addressed through adaptive strategies, including personalized guidance and motivation. This approach demonstrates the potential of integrating religious practices into school routines as a replicable model for character education, fostering morally and socially responsible individuals.